2015
DOI: 10.1080/07391102.2015.1102082
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman and vibrational mode analysis used to predict ligand geometry for docking simulations of a water soluble porphyrin and tubulin

Abstract: The ability to modify the conformation of a protein by controlled partial unfolding may have practical applications such as inhibiting its function or providing non-native photosensitive properties. A water-soluble porphyrin, meso-tetrakis (p-sulfonatophenyl) porphyrin (TSPP), non-covalently bound to tubulin can be used as a photosensitizer, which upon irradiation can lead to conformational changes of the protein. To fully understand the mechanism responsible for this partial unfolding and determine the amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The fact that the decrease of emission intensity from the Trp residues occurs without changes in the absorption of the same residues does suggest that the tubulin undergoes structural changes without chemical changes of the aromatic amino acid residues. A previous docking study suggested that the most likely binding configuration between TSPP and tubulin places one of the sulfonic acid groups of TSPP 6.75 Å away from Trp 346. This binding location is near the region in which tubulin heterodimers bind to each other for polymerization.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The fact that the decrease of emission intensity from the Trp residues occurs without changes in the absorption of the same residues does suggest that the tubulin undergoes structural changes without chemical changes of the aromatic amino acid residues. A previous docking study suggested that the most likely binding configuration between TSPP and tubulin places one of the sulfonic acid groups of TSPP 6.75 Å away from Trp 346. This binding location is near the region in which tubulin heterodimers bind to each other for polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…How can the data from Figure and Figure be reconciled? We have recently shown that binding to proteins distorts the porphyrin macrocycle and changes the group symmetry of the chromophore , from a D 2 h to a ruffled conformation which has no defined point group symmetry. This change may lift TPE symmetry restrictions and allow transitions between orbitals that are otherwise forbidden .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations